EXPERIMENTAL STUDY AND OPTIMISATION OF TECHNOLOGICAL PARAMETERS OF ULTRASONIC WELDING OF SYNTHETIC POLYMERIC MATERIALS - Butovskiy P.M,; Palvannazirova N. , (TADQIQOTLAR.UZ, 2024)
The paper analyzes the possible ways of joining of polymer-based synthetic fabrics. The technological capabilities of seam ultrasonic welding of synthetic fabrics are considered. Experiments on the weldability of polyester, nylon and polypropylene fabrics are carried out. The main parameters of the mode of seam ultrasonic welding of synthetic fabrics are determined.